AttriMIL: Revisiting attention-based multiple instance learning for whole-slide pathological image classification from a perspective of instance attributes - Cai, Linghan; Huang, Shenjin; Zhang, Ye; Lu, Jinpeng; Zhang, Yongbing (Medical image analysis, 2025)
Multiple instance learning (MIL) is a powerful approach for whole-slide pathological image (WSI) analysis, particularly suited for processing gigapixel-resolution images with slide-level labels. Recent attention-based MIL architectures have significantly advanced weakly supervised WSI classification, facilitating both clinical diagnosis and localization of disease-positive regions. However, these methods often face challenges in differentiating between instances, leading to tissue misidentification and a potential degradation in classification performance. To address these limitations, we propose AttriMIL, an attribute-aware multiple instance learning framework. By dissecting the computational flow of attention-based MIL models, we introduce a multi-branch attribute scoring mechanism that quantifies the pathological attributes of individual instances. Leveraging these quantified attributes, we further establish region-wise and slide-wise attribute constraints to dynamically model instance correlations both within and across slides during training. These constraints encourage the network to capture intrinsic spatial patterns and semantic similarities between image patches, thereby enhancing its ability to distinguish subtle tissue variations and sensitivity to challenging instances. To fully exploit the two constraints, we further develop a pathology adaptive learning technique to optimize pre-trained feature extractors, enabling the model to efficiently gather task-specific features. Extensive experiments on five public datasets demonstrate that AttriMIL consistently outperforms state-of-the-art methods across various dimensions, including bag classification accuracy, generalization ability, and disease-positive region localization. The implementation code is available at https://github.com/MedCAI/AttriMIL. [Display omitted] •We present AttriMIL with multi-branch attribute scoring.•Region-wise attribute constraint uses spatial patterns to boost sensitivity.•Slide-wise attribute constraint models instance correlations across WSIs.•Pathology adaptive learning exploits the two constraints for refined features.•Experiments show AttriMIL’s superiority, achieving state-of-the-art performance.